Gambaran Pola Asuh dan Pola Makan Anak Usia 2-5 Tahun di Kelurahan Taipa Kecamatan Palu Utara: Description Of Parental And Children's Food Patterns At Age 2-5 Years In Taipa Sub-District, North Palu District - Elvyrah Faisal; Dwi Erma Kusumawati; Aan Happy Desriani (Poltekkes Kemenkes Palu, 2020)
Children aged 2-5 years are one of the nutrition-prone groups, during this period a decline in growth rate, decreased growth followed by decreased appetite. Based on Riskesdas (2013), there were nutritional status problems in Central Sulawesi, including the prevalence of Stunting by 40%, prevalence of underfive malnutrition by 25%, prevalence of underweight toddlers by 15% and LBW (Low birth weight) by 18%. While the prevalence for the proportion of Stunting children in Palu according to Riskesdas Central Sulawesi in 2013 was 35%, the prevalence of underweight children was 12%, and for cases of malnutrition had a prevalence of 17%. The purpose of this study was to determine the description of parental and food patterns of children aged 2-5 years in Taipa District, North Palu District. This type of research is descriptive. The sample in this study were children aged 2-5 years totaling 77 toddlers. The sampling technique in this study uses the stratified random sampling method. The results showed that parental applied by parents to children is not authoritarian, not democratic and permissive. food sources of carbohydrates that are often consumed are rice, animal protein sources are catfish, chicken eggs, vegetables that are often consumed are Moringa vegetables. There is no fruit that is often consumed by children. The conclusion of this study is the parental applied by parents to children in Taipa Village, North Palu District, the most dominant is democratic parenting, where there are 71 parents who apply this type of fostering and food that is often consumed is rice, catfish, chicken egg and moringa vegetable.